2017
DOI: 10.1002/jcb.26271
|View full text |Cite
|
Sign up to set email alerts
|

Molecular aspects of diabetes mellitus: Resistin, microRNA, and exosome

Abstract: Diabetes mellitus (DM) is known as one of important common endocrine disorders which could due to deregulation of a variety of cellular and molecular pathways. A large numbers studies indicated that various pathogenesis events including mutation, serin phosphorylation, and increasing/decreasing expression of many genes could contribute to initiation and progression of DM. Insulin resistance is one of important factors which could play critical roles in DM pathogenesis. It has been showed that insulin resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
86
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 90 publications
(87 citation statements)
references
References 191 publications
(375 reference statements)
0
86
0
1
Order By: Relevance
“…miRNAs are able to exert their modulation effects via affecting several cellular and molecular pathways and targets such as angiogenesis, growth, differentiation, metastasis, homeostasis, and so on . Dysregulation of miRNAs is associated with initiation and progression of a wide range of diseases such as diabetes, cardiovascular diseases, cancer, neurodegenerative diseases, infection diseases, and depression . Hence, it seems that these molecules could be introduced as diagnostic, prognostic, and therapeutic biomarkers in different diseases .…”
Section: Pancreatic Cancer (Pc)mentioning
confidence: 99%
“…miRNAs are able to exert their modulation effects via affecting several cellular and molecular pathways and targets such as angiogenesis, growth, differentiation, metastasis, homeostasis, and so on . Dysregulation of miRNAs is associated with initiation and progression of a wide range of diseases such as diabetes, cardiovascular diseases, cancer, neurodegenerative diseases, infection diseases, and depression . Hence, it seems that these molecules could be introduced as diagnostic, prognostic, and therapeutic biomarkers in different diseases .…”
Section: Pancreatic Cancer (Pc)mentioning
confidence: 99%
“…These molecules play critical roles in regulation of gene expression in the RNA and protein levels . It has been shown that deregulation of microRNAs is associated with initiation and progression of various diseases such as infectious diseases, cardiovascular diseases, diabetes, neurogenerative diseases, and cancer …”
Section: Microrna and Exosome‐based Vaccinementioning
confidence: 99%
“…Exosomes is other candidate as diagnostic and therapeutic biomarkers for patients with depression. Exosomes are nano‐carriers which carry a variety of cargos such as DNAs, mRNAs, miRNAs, and proteins . These biological vehicles could transfer several vital signals to recipient cells and could lead to change behavior of them .…”
Section: Introductionmentioning
confidence: 99%
“…Exosomes are nano‐carriers which carry a variety of cargos such as DNAs, mRNAs, miRNAs, and proteins . These biological vehicles could transfer several vital signals to recipient cells and could lead to change behavior of them . It has been showed that these nano‐particles may be used as diagnostic and therapeutic tools for depression patients .…”
Section: Introductionmentioning
confidence: 99%